2003
DOI: 10.1080/j.1600-0412.2003.820112.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial ablation with NovaSure™ GEA, a pilot study

Abstract: Preliminary results indicates that the NovaSure GEA System is an effective treatment for DUB, achieving 58% amenorrhea after 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…The rate of amenorrhea was 37.2%, with 90.6% of patients experiencing at least an acceptable decrease in menstrual blood loss. Other studies have reported amenorrhea rates of between 43% and 58% [9,10,14]. In the present study, 93% of participants reported satisfaction with GEA.…”
Section: Discussionsupporting
confidence: 62%
“…The rate of amenorrhea was 37.2%, with 90.6% of patients experiencing at least an acceptable decrease in menstrual blood loss. Other studies have reported amenorrhea rates of between 43% and 58% [9,10,14]. In the present study, 93% of participants reported satisfaction with GEA.…”
Section: Discussionsupporting
confidence: 62%
“…In 1995, when 1 of the earliest EA guidelines was published, a uterine length ,12 cm was recommended to achieve favorable outcomes [6]. This cutoff was typically used by most studies that validated EA [26]. However, a 12-month follow-up of women treated with RFA using 10 cm and 12 cm as a maximum uterine length for inclusion yielded 2 different success rates (98% and 91.5%, respectively) [26,27].…”
Section: Discussionmentioning
confidence: 97%
“…This cutoff was typically used by most studies that validated EA [26]. However, a 12-month follow-up of women treated with RFA using 10 cm and 12 cm as a maximum uterine length for inclusion yielded 2 different success rates (98% and 91.5%, respectively) [26,27]. Accordingly, a maximum uterine length of 10 cm is generally set as a limit for RFA [14].…”
Section: Discussionmentioning
confidence: 99%
“…4 Two additional studies, which together included 156 patients, reported only two mild cases of endometritis in the 2 weeks after the procedure. 5,6 The available literature seems to suggest that severe infectious complications after bipolar radiofrequency endometrial ablations have not been observed. However, not every adverse event is reported in the literature, and clinical trials will not necessarily reveal rare complications.…”
Section: Commentmentioning
confidence: 98%